On becoming a practical theologian: Past, present and future tenses - Graham, Elaine L. (HTS teologiese studies, 2017)
This article takes an autobiographical approach to the development of practical theology as a discipline over the past 30 years, with particular attention to my own context of the United Kingdom (UK). The unfolding of my own intellectual story in relation to key issues within the wider academic discourse provides an opportunity to reflect on some of the predominant themes and trends: past, present and future. Changing nomenclature, from ‘pastoral studies’ to ‘practical theology’, indicates how the discipline has moved from regarding itself as the application of theory into practice, into a more performative and inductive epistemology. This emphasis continues to the present day and foregrounds the significance of the human context and the realities of lived experience, including narrative and autobiography. Whilst the methodological conundrums of relating experience to tradition and theory to practice continue, further challenges are beckoning, including religious pluralism, and so the article closes by surveying the prospects for a multicultural practical theology.